2005
DOI: 10.1111/j.1742-1241.2005.00651.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-induced sarcoidosis

Abstract: Interferons (IFNs) are widely used for the treatment of various medical diseases. They have marked immunomodulatory effects, and many reports have been published associating IFN therapy with the induction of autoimmune phenomena and other disorders of immune regulation such as sarcoidosis. The clinical presentation of IFN-induced sarcoidosis (IIS) is insidious and can be confused with common constitutional side effects of these drugs. The age of onset of IIS is later than that of naturally occurring sarcoidosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 115 publications
1
42
0
Order By: Relevance
“…Despite the lack of evidence for increased pDC frequency or activation in sarcoidosis, IFN-a therapy is a well documented risk factor for development of IFN-induced sarcoidosis (IIS) (112,113), occurring in 5% of patients with chronic hepatitis C treated with IFN-a (114). Also, an IFN-a17 polymorphism, that shows increased IFN-a secretion when whole blood is activated with Sendal virus, has been documented in a cohort of Japanese patients with sarcoidosis (115).…”
Section: Plasmacytoid Dcs Do Not Play a Large Role In Sarcoidosis Patmentioning
confidence: 99%
“…Despite the lack of evidence for increased pDC frequency or activation in sarcoidosis, IFN-a therapy is a well documented risk factor for development of IFN-induced sarcoidosis (IIS) (112,113), occurring in 5% of patients with chronic hepatitis C treated with IFN-a (114). Also, an IFN-a17 polymorphism, that shows increased IFN-a secretion when whole blood is activated with Sendal virus, has been documented in a cohort of Japanese patients with sarcoidosis (115).…”
Section: Plasmacytoid Dcs Do Not Play a Large Role In Sarcoidosis Patmentioning
confidence: 99%
“…The second major organ is the skin. The incidence of skin involvement appears to be much higher that reported in natural sarcoidosis (60% versus 25%) [6,38,41]. The most common skin manifestation is subcutaneous nodules, whereas erythema nodosum, reported to be the most common cutaneous manifestation in typical sarcoidosis, is less frequently observed in IIS.…”
Section: Interferon-induced Sarcoidosismentioning
confidence: 58%
“…Although the incidence of IIS is not known, the prevalence of sarcoidosis in IFN-treated HCV patients has been reported to be rare range from 0.09% to 0.44% [38,39]. The precise prevalence of IIS, however, may be underestimated and difficult to assess because its clinical presentation mimics the constitutional IFN-related adverse effects [6]. Actually, Hoffman et al found a 5% incidence of sarcoidosis in a cohort of 60 patients who participated in a randomized trial of IFN-α therapy for chronic HCV [40] Basically the clinical presentation of IIS resembles that of its idiopathic counterpart.…”
Section: Interferon-induced Sarcoidosismentioning
confidence: 99%
See 2 more Smart Citations